Finance and growth in the EU: New evidence from the harmonisation of the banking industry - Romero-Ávila, Diego (Journal of Banking & Finance, 2007)
This paper presents an investigation of the finance–growth nexus by analysing the growth effect of the harmonisation of banking laws in the EU-15 over the period 1960–2001. The main findings point to the existence of a positive growth impact from banking harmonisation. These results are robust to controlling for other growth determinants, unobserved heterogeneity, potential simultaneity bias and business-cycle effects. The analysis of the transmission channels indicates that the harmonisation process influences economic growth mainly through the increase in the efficiency of financial intermediation.